(untitled) (International relations and international law Journal, 2016)
Cooperation in a multi-vector foreign policy of the Republic of Kazakhstan with European countries is developing both bilaterally and multilaterally in the frame of cooperation with the European Union, OSCE, NATO and others. Hungary plays an important role not only in bilateral and multilateral cooperation, but it also opens up new opportunities for the development of regional cooperation between two countries. This article is dedicated to the main directions of cooperation between Kazakhstan and Hungary in the field of political dialogue, inter-parliamentary cooperation, economy and trade, energy cooperation, cooperation in the field of culture, education and security issues, etc. In analyzing the prospects of cooperation between two countries, the article examines the factors impeding cooperation and makes recommendations for the development of new areas of cooperation.